2022
DOI: 10.1039/d2cs00206j
|View full text |Cite
|
Sign up to set email alerts
|

Progress in organocatalysis with hypervalent iodine catalysts

Abstract: Hypervalent iodine compounds as environmentally friendly and relatively inexpensive reagents have properties similar to transition metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 208 publications
0
50
0
Order By: Relevance
“…Effective hypervalent iodine(III)-catalyzed processes (for example, oxidative double C=C bond functionalization, oxidative cyclizations, CH-functionalization of carbonyl compounds, etc.) employing mainly peroxoacids or electric current as terminal oxidants were developed [139][140][141][142][143][144][145]. The key step in the catalytic cycle involving aryl iodides is the formation of iodine(III) species.…”
Section: Hypervalent Iodine Catalysismentioning
confidence: 99%
“…Effective hypervalent iodine(III)-catalyzed processes (for example, oxidative double C=C bond functionalization, oxidative cyclizations, CH-functionalization of carbonyl compounds, etc.) employing mainly peroxoacids or electric current as terminal oxidants were developed [139][140][141][142][143][144][145]. The key step in the catalytic cycle involving aryl iodides is the formation of iodine(III) species.…”
Section: Hypervalent Iodine Catalysismentioning
confidence: 99%
“…8,9 Different chiral iodoarenes have been utilized as organocatalysts in several impressive stereoselective transformations. [10][11][12] Furthermore, relatively weak iodine-ligand bonds in HIRs allow their use in radical chemistry as well. 13 Homolysis of HIRs resulting from their photoactivation under UV mercury lamp has been studied since the late 80s.…”
Section: Introductionmentioning
confidence: 99%
“…The spirolactone framework is not only a potentially useful subunit in natural products and bioactive compounds, such as spiroindicumide A, spiroindicumide B, lagoditerpene E, norcrocrassinone, pathylactone, arteannuin B, petuniolide (C and E), and petunianine B (Figure ), but also plays a key role in developing more novel and versatile chiral auxiliaries for catalytic enantioselective oxidative dearomatization reactions. Recently, many research groups have reported chiral hypervalent iodine-catalyzed intramolecular spirolactonization. , In general, the hypervalent iodine-promoted dearomatization can be achieved at either ortho , or para , positions of the starting phenols, resulting in the formation of either 2,4-cyclohexadienones or 2,5-cyclohexadienones, respectively (Scheme ). To the best of our knowledge, the formation of a spirolactone ring moiety at the meta -position of phenol via a dearomatization process has been rarely accomplished.…”
Section: Introductionmentioning
confidence: 99%